A structural model of academic performance based on the meaning of education and academic optimism for students of medical sciences: The mediating role of stress. - Mahdieh, Neda; Hooman, Farzaneh; Asgari, Parviz (Research & Development in Medical Education, 2024)
Background: Academic performance is a major concern of the education system and indicates its success in goal-setting and meeting individual needs. The present study aimed to investigate the mediating role of stress in the relationship between the meaning of education and academic optimism with academic performance in students of medical sciences. Methods: This was a descriptive correlational study. The statistical population comprised all students of medical sciences at Ahvaz Jundishapur University of Medical Sciences, Iran (2022-2023). The study sample consisted of 301 students who were selected using convenience sampling and the Meaning of Education Questionnaire, the Academic Optimism Questionnaire, and the Perceived Stress Scale were administered. The students' last-semester grade point average (GPA) was used as an indicator of their academic performance. The proposed model was evaluated via structural equation modeling (SEM), and the bootstrap test was used to study the indirect relationships. Results: The results revealed significant positive associations between the meaning of education and academic performance (β = 0.19, P = 0.003) and between academic optimism and academic performance (β = 0.18, P = 0.007) among medical students. Additionally, the meaning of education had a direct negative effect on stress (β = -0.36, P = 0.001), while academic optimism also exhibited a direct negative effect on stress (β = -0.43, P = 0.001). Furthermore, stress had a significant negative impact on academic performance (β = -0.18, P = 0.027). The associations between the indirect paths and academic performance were also significant with the mediating role of stress (P < 0.05). Conclusion: Accordingly, the proposed model has a good fit and can be useful in identifying the factors affecting academic performance and stress in the students of medical sciences and in developing and designing programs to prevent academic underachievement and improve academic performance in the target group.